ANALISIS SARANA DAN PRASARANA LABORATORIUM BIOLOGI DAN PELAKSANAAN KEGIATAN PRAKTIKUM BIOLOGI DALAM MENDUKUNG PEMBELAJARAN BIOLOGI KELAS XI - Anita Christy Simatupang; Aida Fitriani Sitompul (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the completeness of facilities and infrastructure of biological laboratories, to know the intensity and implementation of biological practice, and to know the influence of laboratory facilities and infrastructure in supporting biology learning in SMA Negeri 1 Percut Sei Tuan. The population used as the object of research is all students of class XI majoring in science amounted to 6 classes and biology subject teachers in SMA Negeri 1 PercutSei Tuan who teaches in class XI majoring in IPA amounting to 2 people. The sample used in this study were teachers and students. Student sampling technique in this research is done by random sampling (34 random sampling) where every element of entire population have equal opportunity or opportunity to become sample of research. Sampling technique for teachers is done in total sampling as much as 2 people. The result of data analysis obtained is the completeness of laboratory facilities and infrastructure at school is good with percentage 66,63%, the implementation of biology practicum based on questionnaire given to teacher and student of SMA Negeri 1 Percut Sei Tuan have average that is 67,5% (teacher ) and 72.43% (students), the implementation of practicum activities in SMA Negeri 1 Percut Sei Tuan only 8 times practicum with a percentage of 40% (less good).Keywords: Laboratory Facilities and Infrastructure, Practical Implementation, Biology Learning.